Q is for quinoa - Drucker, Adam G.; Ramírez, M. (Economist, 2016)
Poor Andean farmers are not marginal producers of quinoa once their broader socio-economic contribution to society is taken into account (“Against the grain”, May 21st). Niche market-focused poverty alleviation strategies based on production of the 10-15 main commercial varieties need to be replaced with broader strategies that permit farmers to play a role selling not only agricultural products but also ecosystem conservation services of national and global importance. For example, maintaining the genes of thousands of quinoa varieties for future climate change adaptation, as well as for combating emerging pests and diseases. Recognising the importance of “going with the diversity grain” would also help to ensure that Peruvians can make healthy food consumption choices that are compatible with living in a megabiodiverse country.